2011
DOI: 10.1002/hrdq.20070
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of the impact of positive psychological capital on employee attitudes, behaviors, and performance

Abstract: The positive core construct of psychological capital (or simply PsyCap), consisting of the psychological resources of hope, efficacy, resilience, and optimism, has recently been demonstrated to be open to human resource development (HRD) and performance management. The research stream on PsyCap has now grown to the point that a quantitative summary analysis of its impact on employee attitudes, behaviors, and especially performance is needed. The present meta‐analysis included 51 independent samples (representi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

90
1,317
7
70

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,308 publications
(1,484 citation statements)
references
References 63 publications
90
1,317
7
70
Order By: Relevance
“…Evidence has shown that, as a result, the employee will feel reduced levels of emotional exhaustion because they are better able to cope with the demands of their job role (Xanthopoulou et al, 2007), and will feel lower levels of change-related anxiety because building psychological resources helps employees to be better able to adapt to changes in the work environment and maintain positive morale and performance in the face of uncertainty, which further increases retention (Avey, Reichard, Luthans and Mhatre, 2011).…”
Section: The Mediating Role Of Work Attitudes In the Relationship Betmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has shown that, as a result, the employee will feel reduced levels of emotional exhaustion because they are better able to cope with the demands of their job role (Xanthopoulou et al, 2007), and will feel lower levels of change-related anxiety because building psychological resources helps employees to be better able to adapt to changes in the work environment and maintain positive morale and performance in the face of uncertainty, which further increases retention (Avey, Reichard, Luthans and Mhatre, 2011).…”
Section: The Mediating Role Of Work Attitudes In the Relationship Betmentioning
confidence: 99%
“…In particular, HR practitioners should consider the psychological needs of the individual employee (Bakker and Demerouti, 2008;Parker and Griffin, 2011), and should focus on enriching the experience and quality of training (Lee and Bruvold, 2003). For example, organizations could better reap the benefits of training by incorporating mindfulness and coaching activities that aim to increase meaningfulness and work role fit (Leroy, Anseel, Dimitrova and Sels, 2013) and developing capabilities, such as psychological capital, that enhance positive psychological states and attitudes (Avey et al, 2011). Moreover, line managers should seek to understand the career goals and motives of their direct reports;…”
Section: Implications For Practice and Conclusionmentioning
confidence: 99%
“…A recent meta-analysis indicates that this PsyCap has a positive relationship with desirable employee attitudes, behaviors, and performance (Avey, Reichard, Luthans & Mhatre, 2011). Specifically, over the past few years, PsyCap has been shown to be developable in employees (Luthans, Avey, Avolio & Peterson, 2010;Luthans, Avey & Patera, 2008) and to cause performance Peterson, Luthans, Avolio, Walumbwa & Zhang, 2011).…”
Section: Positive Organizational Behavior and Psychological Capitalmentioning
confidence: 99%
“…This consideration is determined both by the competitive advantage it offers for organizations, because it is related to positive attitudes and behaviours in workers, and because it represents a personal resource open to change and development (Avey, Reichard, Luthans & Mhatre, 2011;Luthans, Avey, Avolio & Peterson, 2010). Moreover, uncertainties and continuous changes in the labour market require workers to have psychological resources that increase their personal and professional efficacy, and allow themselves to confront organisational demands.…”
Section: Introductionmentioning
confidence: 99%